Handbook of Socioeconomic Determinants of Occupational Health 2020
DOI: 10.1007/978-3-030-05031-3_17-1
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Safety Climate and Occupational Health

Abstract: Psychosocial safety climate (PSC) is a facet-specific organizational climate that relates to employee psychological safety and health. Since the proposal of PSC over 10 years ago, PSC has received significant attention from researchers interested in the effect of the meso-level organizational context and its relationship with occupational health and safety. The theory of PSC is an emergent phenomenon which proposes that organizations differ in terms of their prioritization of psychological aspects of individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 68 publications
1
21
0
1
Order By: Relevance
“…Thus, a parsimonious version of the scale, PSC-4, has been introduced, consisting of one item from each of the theoretically based four domains described above [9,25]. The results using three time-lagged Australian samples demonstrated satisfactory predictive validity and reliability of the PSC-4 [25], but more studies in different organizational and cultural contexts are needed for further empirical testing of the ultrashort measure [10].…”
Section: Assessing the Psychosocial Safety Climatementioning
confidence: 99%
See 2 more Smart Citations
“…Thus, a parsimonious version of the scale, PSC-4, has been introduced, consisting of one item from each of the theoretically based four domains described above [9,25]. The results using three time-lagged Australian samples demonstrated satisfactory predictive validity and reliability of the PSC-4 [25], but more studies in different organizational and cultural contexts are needed for further empirical testing of the ultrashort measure [10].…”
Section: Assessing the Psychosocial Safety Climatementioning
confidence: 99%
“…The PSC manifests the true priorities of an organization and emphasizes the senior management’s commitment and priority given to employees’ psychological well-being and security [ 9 ]. Thus, in organizations with high PSC, the managers give a higher priority to work conditions that protect and enhance employee psychological health instead of solely focusing on productivity [ 10 ]. According to the theory, PSC is regarded as an upstream organizational factor predicting work-related psychosocial risks, e.g., demands and resources [ 9 ], and is therefore referred to as the “cause of the causes” of work stress [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PSC concerns an organizational climate referring to prioritization and commitment of all parties within the organization ((top) management, employees, health and safety representatives) to employee well-being (Dollard et al, 2012). Although, up till now, the effects of climate factors on the success of intervention projects has received little research attention, a more favorable PSC has been related to better job factors and employee wellbeing (Loh et al, 2020). Furthermore, in a pilot study by Dollard (2012) regarding a participative intervention, it was found that in teams with a more favorable PSC, employees attended more workshop sessions, rated the quality of these workshops higher (e.g., ability to discuss issues openly, ability to determine actions to address stress factors) and indicated more progress in the intervention project (e.g., "to what extent are actions from your workgroup action plans being addressed").…”
Section: Psychosocial Safety Climate Interventionmentioning
confidence: 99%
“…We aim to contribute to the literature in three ways. First, we extend the PSC theoretical framework (Dollard and Bakker, 2010 ; Zadow and Dollard, 2016 ; Zadow et al, 2019 ; Loh et al, 2020 ; Dollard and Bailey, 2021 ) to examine the impact of a psychologically healthy work climate (i.e., high PSC) on workplace creativity and innovation. An extensive review has highlighted the role of contextual individual psychosocial work design factors such as job control, coworker support, customer trust, and positive leadership in promoting employees' innovation and creativity (Brattström et al, 2012 ; Zhou and Hoever, 2014 , 2022 ).…”
Section: Introductionmentioning
confidence: 99%